The SAGE handbook of tourism management - Cooper, Chris; Volo, Serena; Gartner, William; Scott, Noel (SAGE Publications Ltd, 2018)
The SAGE Handbook of Tourism Management is a critical, state-of-the-art and authoritative review of tourism management, written by leading international thinkers and academics in the field. With a strong focus on applications of theories and concepts to tourism, the chapters in this volume are framed as critical synoptic pieces covering key developments, current issues and debates, and emerging trends and future considerations for the field. Part One: Approaching Tourism Part Two: Destination Applications Part Three: Marketing Applications Part Four: Tourism Product Markets Part Five: Technological Applications Part Six: Environmental Applications This handbook offers a fresh, contemporary and definitive look at tourism management, making it an essential resource for academics, researchers and students
Keywords: Tourism -- Management; Tourismus; Management